2021
DOI: 10.1111/cogs.13043
|View full text |Cite
|
Sign up to set email alerts
|

Constrained Choice: Children's and Adults’ Attribution of Choice to a Humanoid Robot

Abstract: Young children, like adults, understand that human agents can flexibly choose different actions in different contexts, and they evaluate these agents based on such choices. However, little is known about children's tendencies to attribute the capacity to choose to robots, despite increased contact with robotic agents. In this paper, we compare 5-to 7-year-old children's and adults' attributions of free choice to a robot and to a human child by using a series of tasks measuring agency attribution, action predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“…In support of this, we found that by around 8 years old, children began to recognize that a technology's programming limits them from performing certain actions. By 10 years old, children began to recognize that a technology's programming can even limit it from avoiding harm, similar to adults’ beliefs about technologies’ limitations (Flanagan et al, 2021). Anecdotal evidence from children's spontaneous comments during the interview offers some support for this idea as well.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In support of this, we found that by around 8 years old, children began to recognize that a technology's programming limits them from performing certain actions. By 10 years old, children began to recognize that a technology's programming can even limit it from avoiding harm, similar to adults’ beliefs about technologies’ limitations (Flanagan et al, 2021). Anecdotal evidence from children's spontaneous comments during the interview offers some support for this idea as well.…”
Section: Discussionmentioning
confidence: 99%
“…Our methodology was an interview format, including questions from prior studies that investigated different aspects of children's agency beliefs of technologies and that had different question formats (Brink et al, 2019; Chernyak & Gary, 2016; Flanagan et al, 2021; Severson & Lemm, 2016). This was an initial step towards creating a comprehensive questionnaire to investigate children's technology beliefs, but more work is needed to address the current limitations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some recent work is broadly consistent with the possibility that people expect machines to differ from humans in how they prioritize information when making decisions. For example, children and adults expect robots to make different choices than humans when faced with the same situation (Flanagan et al, 2021). Also, people often rate computers and robots as less able than humans to have many mental states, but especially desires and emotions (Bigman & Gray, 2018;Gray et al, 2007;Haslam et al, 2008;Weisman et al, 2017).…”
Section: Introductionmentioning
confidence: 99%